Coordination games played by children and teenagers: On the influence of age, group size and incentives - Daniela Glätzle-Rützler; Matthias Sutter; Claudia Zoller (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
Efficient coordination is a major source of efficiency gains. We study in an experimental coordination game with 718 children and teenagers, aged 9 to 18 years, the strategies played in pre-adulthood. We find no robust age effects in the aggregate, but see that smaller group sizes and larger incentives increase the likelihood of choosing the efficient strategy. Beliefs play an important role as well, as subjects are more likely to play the efficient strategy when they expect others to do so as well. Our results are robust to controlling for individual risk-, time-, and social preferences.
Keywords: C91; 330; coordination game; age; group size; incentives; children; experiment